Conversations With Myself - Mandela, Nelson (New York Picador, 2011)
Nelson Mandela is one of the most inspiring and iconic figures of our age. Now, after a lifetime of recording thoughts and events, hardships an victories, he has opened his personal archive, which offers unprecedented insight into his remarkable life. ... An intimate journey from the first stirrings of political consciousness to his galvanizing role on the world stage, Conversations with Myself is a rare chance to spend time with Nelson Mandela the man, in his own voice: direct, clear private"--Publisher.
Include Illustrations and Index